Decay rate of Eschericha Coli in wastewater : effects of temperature and substrate - Ling, T. Y.; Tan, W. S.; Kasing, Apun (Proceeding of the 3rd Regional Conference on Natural Resources in the Tropics (NRTrop3), 2009, 2009)
In intensive animal farming, wastewater produced has to be treated in oxidation ponds prior to release into the rivers. The decay of fecal bacteria in such nutrient rich wastewater in the tropics would provide knowledge on the retention period required for safe release. Therefore, the objective of this study was to investigate the effect of nutrients and temperature on the decay rate of E.coli in animal farm wastewater. A laboratory experiment was conducted on fresh animal farm wastewater (UW), diluted wastewater (DW), sterile wastewater (SW), and physiological saline (PS). Results show that at both temperatures of 20 Degree Celsius and 30 Degree Celsius, the trend of decrease in E.coli population was in decreasing order of UW>DW>PS>SW. Initial population of 10^6 cfu/ml in DW dropped to undetectable level in 11 days and 7 days respectively. However, in UW, it persisted longer where at 20 Degree Celsius, it was still detectable after 20 days and at 30 Degree Celsius it was undetectable after 11 days. There was an increase in the population of E.coli in SW resulting in final population that was higher than the initial population. Regression indicated that the decay of E.coli in UW and DW fitted the first order decay model with R^2 of 0.94-0.98. Decay rates of E.coli ranged from 0.23 to 0.94 per day. Decay rates at 30 Degree Celsius were higher than decay rates at 20 Degree Celsius in all treatments. E.coli survived better in SW than PS due to the availability of nutrients. Higher decay rates in UW compared to SW indicates the role of predation and competition in the decrease of E.coli in wastewater. Results of this study indicate that if the temperature of the pond wastewater is maintained at 30 Degree Celsius, it would be safe to release the water after 11 days retention. However, if the temperature drops below that, longer retention period is required.